2007
DOI: 10.1021/ma0704919
|View full text |Cite
|
Sign up to set email alerts
|

Micellization Behavior of Complex Comblike Block Copolymer Architectures

Abstract: Complex comblike block copolymers of various architectures containing polystyrene, PS, and polyisoprene, PI, or polybutadiene, PB, components were synthesized by anionic polymerization high-vacuum techniques and the macromonomer strategy. Their micellization behavior was studied in n-decane, a selective solvent for the PI or PB blocks, and in N,N′-dimethylacetamide, DMA, selective for the PS blocks. Utilizing static and dynamic light scattering techniques, parameters such as the aggregation number and the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 90 publications
2
69
0
1
Order By: Relevance
“…However, multicompartment micelles such as core-shell-corona and segmented-worm micelle formed by multiblock copolymer are observed [8]. Recently, various synthetic methods have been developed to synthesize copolymers of complex architectures, such as star-like, and branched copolymers [9][10][11][12][13]. It is found that copolymers with intricate structures often display distinct aggregative behaviors from those of their linear counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, multicompartment micelles such as core-shell-corona and segmented-worm micelle formed by multiblock copolymer are observed [8]. Recently, various synthetic methods have been developed to synthesize copolymers of complex architectures, such as star-like, and branched copolymers [9][10][11][12][13]. It is found that copolymers with intricate structures often display distinct aggregative behaviors from those of their linear counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental [13] and theoretical results demonstrate that there is a large parameter space (e.g. block lengths, choice of monomers, and chain architecture) to explore the formation of micelles.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior may be attributed to differences in the quality of the solvents, but, in addition, it may reflect the general conclusion drawn in graft copolymers that the degrees of aggregation are reduced upon increasing the number of soluble chains. 104 The micellization behavior of a PS-PI diblock copolymer with M w ¼ 80 700 and 54% wt PS was reported in the literature in DMA and thus can be compared with sample 50/50. 105 It is obvious that the diblock copolymer has a much higher N w value compared with the corresponding asymmetric miktoarm star, because of the difference in polymer topology.…”
Section: Micellization Behavior In Dmamentioning
confidence: 99%
“…The micellization of amphiphilic block copolymers can be tailored by changing the block nature, block lengths, composition, or architecture of amphiphilic copolymers. [73][74][75] Similar to precipitation polymerization, this method employs block copolymers that selfassemble in aqueous media. When the polymer concentration exceeds the critical micelle concentration (CMC), nanogels could be produced by adding a crosslinking agent or triggering a crosslinking functionality on the polymer chain.…”
Section: Self-assembly Of Polymers Into Micro/ Nanogelsmentioning
confidence: 99%